Manifesto : being the book of the Federation of Progressive Societies and Individuals - Joad, C.E.M.; Wells, H.G. (London : George Allen & Unwin, 1934)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Federation of Progressive Societies and Individuals; maatschappelijke vraagstukken